Pharmacokinetic and Pharmacodynamic Interactions between Food or Herbal Products and Oral Anticoagulants: Evidence Review, Practical Recommendations, and Knowledge Gaps - Talasaz, Azita H.; McGonagle, Bridget; HajiQasemi, Mohsen; Ghelichkhan, Zahra A.; Sadeghipour, Parham; Rashedi, Sina; Cuker, Adam; Lech, Tara; Goldhaber, Samuel Z.; Jennings, Douglas L.; Piazza, Gregory; Bikdeli, Behnood (Seminars in Thrombosis and Hemostasis, 2024)
Interactions between food and oral anticoagulants (OACs), particularly vitamin K antagonists such as warfarin, are widely recognized and may also be clinically relevant for direct OACs. Pharmacokinetic and pharmacodynamic interactions with food or herbs can lead to anticoagulation potentiation, increased risk of bleeding, or reduced drug efficacy, all compromising patient safety. We conducted a systematic search for randomized controlled trials (RCTs) on PubMed for assessments of interactions between OACs and various ingestants. Since the RCT evidence was slim, we also reviewed prospective longitudinal studies, case series, and case reports to identify possible associations between foods and anticoagulation therapy. We referred to basic or translational studies that shared putative explanations for such interactions, but we failed to identify high-quality evidence in most cases. The limited evidence, small sample size of the studies, conflicting results, and possible heterogeneity in the contents of herbal products prevent a conclusive assessment of these interactions. Existing evidence suggests that (1) cranberry juice consumption (up to 240 mL/d and probably even more) with warfarin is safe; (2) use of green leafy vegetables with a high daily content (more than 250 µg) of vitamin K should be cautioned for patients receiving warfarin, because it may decrease warfarin efficacy. It is also advisable for patients to maintain highly constant intake of green leafy vegetables to ensure stable warfarin effectiveness; (3) ginger, even in small quantities (excluding commercial ginger-flavored beverages, which contain only negligible amounts of ginger), and mango (more than one fruit) can both potentiate warfarin effects; (4) patients taking OACs should avoid St. John's wort due to diminished anticoagulant effect; and (5) consumption of less than 240 mL of grapefruit juice daily is unlikely to interact with OACs. Future longitudinal observational cohort studies and RCTs with larger sample sizes are needed to study specific interactions between food or herbal products and OACs.
Keywords: oral anticoagulants; herb-drug interactions; food-drug interactions; warfarin; direct oral anticoagulants; pharmacokinetics; pharmacodynamics